2021
DOI: 10.1016/j.pt.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of Protein Phosphatase 1 in Plasmodium

Abstract: Protein Phosphatase type 1 (PP1) forms a wide range of Ser/Thr specific phosphatase holoenzymes which contain one catalytic subunit (PP1c), present in all eukaryotic cells, associated with variable subunits known as regulatory proteins. It has recently been shown that regulators take a leading role in the organization and the control of PP1 functions. Many studies have addressed the role of these regulators in diverse organisms including humans and investigated their link to diseases. In this review we summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 87 publications
(129 reference statements)
0
16
0
Order By: Relevance
“…Other biochemical studies in Plasmodium have identified numerous PP1-interacting partners (PIPs) that are structurally conserved and regulate PP1 activity, including LRR1 (a human SDS22 orthologue), Inhibitor 2 and Inhibitor 3. Other PIPs including eif2β, and GEXP15 have also been identified 9, 28, 30, 31 . However, little is known regarding how PP1 is involved in regulating mitosis and meiosis in the absence of CDC14 and CDC25.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Other biochemical studies in Plasmodium have identified numerous PP1-interacting partners (PIPs) that are structurally conserved and regulate PP1 activity, including LRR1 (a human SDS22 orthologue), Inhibitor 2 and Inhibitor 3. Other PIPs including eif2β, and GEXP15 have also been identified 9, 28, 30, 31 . However, little is known regarding how PP1 is involved in regulating mitosis and meiosis in the absence of CDC14 and CDC25.…”
Section: Introductionmentioning
confidence: 95%
“…Other biochemical studies in Plasmodium have identified numerous PP1-interacting partners (PIPs) that are structurally conserved and regulate PP1 activity, including LRR1 (a human SDS22 orthologue), Inhibitor 2 and Inhibitor 3. Other PIPs including eif2β, and GEXP15 have also been identified 9, 24, 31, 32, 33 . Synthetic peptides containing the RVxF motif of Inhibitor 2 and Inhibitor 3, and the LRR and the LRR cap motif of Pf LRR1 significantly reduce P. falciparum growth in vitro 34, 35 and regulate Pf PP1 phosphatase activity 35, 36, 37 .…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations